Endemism in recently diverged angiosperms is associated with polyploidy - Sara Villa; Matteo Montagna; Simon Pierce (Plant Ecology, 2022)
Endemic (range restricted or precinctive) plant species are frequently observed to exhibit polyploidy (chromosome set duplication), which can drive shifts in ecology for angiosperms, but whether endemism is generally associated with polyploidy throughout the flowering plants has not been determined. We tested the hypothesis that polyploidy is more frequent and more pronounced (higher evident ploidy levels) for recently evolved endemic angiosperms. Chromosome count data, molecular dating and distribution for 4210 species (representing all major clades of angiosperms and including the largest families) were mined from literature-based databases. Upper boundary regression was used to investigate the relationship between the maximum number of chromosomes and time since taxon divergence, across clades and separately for families, comparing endemic with non-endemic species. A significant negative exponential relationship between maximum number of chromosomes and taxon age was evident across angiosperms ( R 2 adj = 0.48 for all species, R 2 adj = 0.49 for endemics; R 2 adj = 0.44 for non-endemics; p always < 0.0001), recent endemics demonstrating greater maximum chromosome numbers ( y intercept = 164 cf. 111) declining more rapidly with taxon age (decay constant = 0.12, cf. 0.04) with respect to non-endemics. The majority of families exhibited this relationship, with a steeper regression slope for endemic Campanulaceae, Asteraceae, Fabaceae, Poaceae, Caryophyllaceae and Rosaceae, cf. non-endemics. Chromosome set duplication is more frequent and extensive in recent angiosperms, particularly young endemics, supporting the hypothesis of recent polyploidy as a key explanation of range restriction. However, as young endemics may also be diploid, polyploidy is not an exclusive driver of endemism.